Analisis Keragaman Genetik Temulawak (Curcuma xanthorrhiza Roxb.) Menggunakan Penanda Amplified Fragment Length Polymorphism (AFLP) - damayanti, dini; tajuddin, teuku; purwoko, devit; zulaeha, siti; suharsono, suharsono (Badan Pengkajian dan Penerapan Teknologi, 2012)
Curcuma xanthorrhiza Roxb, which is well-known as Java turmeric, has been extensively used in pharmaceutical industries in Indonesia. In spite of this commercial value, the identity of this species is commonly mistaken from other similar orange rhizomes Curcuma. Correct identity of these species is vital in pharmaceutical industries. The objective of the study was to determine genetic diversity of 32 accession Curcuma xanthorrhiza Roxb. Genomic DNA was extracted from leaf using Sodium Dodesyl Sulphate (SDS) modification. Amplified fragment length polymorphism (AFLP) was carried out according to the protocol ofAFLPTM plant mapping kit and the final polymerase chain reaction (PCR) products were separated using The Agilent 2100 Bioanalyzer. The number of fragment produced by 12 pairs primer combination of AFLP ranged from 42 to 60 with an average of 52. Data obtained was analyzed by the NTSys program. From the AFLP amplification on 32 DNA samples, it was proven that the accession of Curcuma xanthorrhiza Roxb. had a high degree of diversity. Based on analysis of AFLP and unweighted pair group with arithme average (UPGMA) it was shown that the accession of Curcuma xanthorrhiza Roxb. could be grouped into two cluster at relative ecludian distance of 0.10 (10%). Cluster I for accession from Palembang, Pacitan and Ciamis 2. Cluster II for accession from Makale, Pontianak, Kulonprogo, Mataram, Boyolali, Salatiga, Sumberejo, Bali, P. Seram, Sentolo, Purworejo, Samas Bantul, Ciamis1, Blora, Semarang, Poso, Kalsesl, Tagari, Merapi Farm, Salakaria, NTB, Menoreh, Karang Anyar, Mangunan, Medan, Toraja, dan Solok.